2021
DOI: 10.1021/acs.nanolett.0c05021
|View full text |Cite|
|
Sign up to set email alerts
|

Excitonic Complexes in n-Doped WS2 Monolayer

Abstract: We investigate the origin of emission lines apparent in the low-temperature photoluminescence spectra of n-doped WS 2 monolayer embedded in hexagonal BN layers using external magnetic fields and first-principles calculations. Apart from the neutral A exciton line, all observed emission lines are related to the negatively charged excitons. Consequently, we identify emissions due to both the bright (singlet and triplet) and dark (spin- and momentum-forbidden) negative trions as well as the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
68
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 40 publications
15
68
0
Order By: Relevance
“…For instance, emission lines corresponding to the dark excitons 170,182,185,[204][205][206] , dark trions 176,178,181,205,207 , phonon replicas of spin-and momentum-forbidden dark excitons 179,180 , and phonon replicas of positive and negative dark trions 177,179,189,207,208 have been identified in monolayer WSe2 magneto PL, on the bases of their observed g factors (ranging from -6 to -13). Another recent work also identifies these lines in hBN-encapsulated monolayer WS2 209 . We discuss some of these features in the following.…”
Section: Neutral 'Bright' Excitons In Tmdcsmentioning
confidence: 76%
See 3 more Smart Citations
“…For instance, emission lines corresponding to the dark excitons 170,182,185,[204][205][206] , dark trions 176,178,181,205,207 , phonon replicas of spin-and momentum-forbidden dark excitons 179,180 , and phonon replicas of positive and negative dark trions 177,179,189,207,208 have been identified in monolayer WSe2 magneto PL, on the bases of their observed g factors (ranging from -6 to -13). Another recent work also identifies these lines in hBN-encapsulated monolayer WS2 209 . We discuss some of these features in the following.…”
Section: Neutral 'Bright' Excitons In Tmdcsmentioning
confidence: 76%
“…It needs to be checked if it is the case for the dark exciton in MoS2 as well. Finally, phonon replicas of dark excitons, for instance in Figure 9 are observed energetically below the dark excitons in monolayer WS2 and WSe2 on the basis of their observed g factors (either about 9 or 12), energetic locations, and valley polarization 177,179,180,209 . Therefore, magnetooptical spectroscopy has been crucial in the identification of PL peaks previously under debate 87,166,203 .…”
Section: Neutral 'Dark' Excitons In Tmdcsmentioning
confidence: 95%
See 2 more Smart Citations
“…Both the experiment and theoretical calculations demonstrated that the lowest energy optical excitations in a doped TMDC ML are often associated with trions [10][11][12][13][14][15][16][17][18][19] . A sophisticated band structure with two direct band gaps at the K and K = −K points of the Brillouin zone and the presence of the spin-valley locking effect [26][27][28][29] makes it possible to realize various trionic states in TMDC ML's [30][31][32][33][34][35][36][37][38][39][40][41][42]. Commonly, they are classified by spin and valley quantum numbers and can be dark and bright depending on their combination.…”
mentioning
confidence: 99%